2011
DOI: 10.1016/j.jad.2011.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between lifetime stressful life events and the onset of major depression in Chinese women

Abstract: BackgroundIn European and US studies, patients with major depressive disorder (MDD) report more stressful life events (SLEs) than controls, but this relationship has rarely been studied in Chinese populations.MethodsSixteen lifetime SLEs were assessed at interview in two groups of Han Chinese women: 1970 clinically ascertained with recurrent MDD and 2597 matched controls. Diagnostic and other risk factor information was assessed at personal interview. Odds ratios (ORs) were calculated by logistic regression.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
4
31
0
Order By: Relevance
“…Childbirth‐related problems, such as miscarriage and giving birth to daughters, also result in more depressive symptoms among young Chinese women (Qiu and Xiao ; Ramashwar ; Tao et al. ). Moreover, traditional Chinese religions, especially Chinese folk religions and Confucianism, typically serve as tools for perpetuating gender discrimination in the patrilineal society (Law ).…”
Section: Discussionmentioning
confidence: 99%
“…Childbirth‐related problems, such as miscarriage and giving birth to daughters, also result in more depressive symptoms among young Chinese women (Qiu and Xiao ; Ramashwar ; Tao et al. ). Moreover, traditional Chinese religions, especially Chinese folk religions and Confucianism, typically serve as tools for perpetuating gender discrimination in the patrilineal society (Law ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a case-control study from mainland China also found that patients with major depressive disorders were more likely to have experienced stressful life events than controls, and reported a dose-response relationship between stressful life events and major depressive disorders [24]. Therefore, an assessment of stressful life events has been included in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the differences in interhemispheric coherence in the frontotemporal areas between the two groups may result from the different susceptibility of the frontolimbic circuitry function to stress 40. These findings suggest that patients with ADJ may be more vulnerable to the negative stress in excess of what would be expected from exposure to a stressor1 although patients with MDD may show marked distress during the illness period 41-43…”
Section: Discussionmentioning
confidence: 99%